Die Mar̈kte fur̈ Eier und Gefug̈elfleisch - Karl Frenz (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– (6) Animal welfare and environmental considerations are slowly gaining ground with regard to egg and poultry production. They are no longer a matter of tiny consumer groups in the more affluent societies but rather begin to affect big industries, international trade and world trade policy (WTO). Nevertheless, the vast majority of producing countries are concerned primarily about increasing production in order to improve human welfare.
Keywords: 330